HIGH-FAT DIET-INDUCED OXIDATIVE STRESS AND ITS IMPACT ON METABOLIC SYNDROME: A REVIEW - Kesh, Swaraj Bandhu; Sarkar, Debashree; Manna, Krishnendu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Environmental factors such as high saturated fat content in a diet affect pro- and antioxidative balances in metabolic tissues. High-dietary fat intake promotes the development of obesity and metabolic disorders in humans and rodents as a result of disproportion between energy intake and energy expenditure. The dreaded events of high-fat diet (HFD) are obesity, hypertension, cardiovascular and cerebrovascular anarchy, Type II diabetes, infertility, and even cancer. HFD - induced systemic oxidative stress insults an imbalance between oxidants derivatives production and antioxidants defenses. Reactive oxygen species are mostly reasoned to be detrimental for health. Many evidences regarding HFD - elicited oxidative stress gathered over the past few years based on established correlations of biomarkers or end-products of free-radical-mediated oxidative stress. The hypothesis that oxidative stress plays a prodigious role in the development of metabolic disorders, especially insulin resistance, hyperlipidemia, cardiovascular disease or hepatic steatosis, and steatohepatitis. In this review, we elucidated the mechanistic links between HFD - induced oxidative stress and its impact on metabolic complications development. Keywords: Adenosine monophosphate-activated protein kinase, Complications, High-fat diet, Metabolic syndrome, Oxidative stress.